ANALISIS FITOKIMIA DAN UJI TOKSISITAS AIR SADAPAN BATANG PISANG MERAH (Musa acuminata Colla ‘Red Dacca’) - Nurul Ade Safitri; Wa Ode Mulyana; Abraham Rahman (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The ethnobotanical utilization of tap water from the pseudo stem of red banana (Musa acuminata Colla ‘Red Dacca’) to accelerate wound healing and treat infections whose scientific safety profile has not been explored is the background of this research. This operational problem triggers the lack of validation of clinical efficacy standards and the absence of draft information regarding the toxicity threshold of this natural material. The main focus of this scientific study is to analyze the qualitative secondary metabolite content and test its specific toxicity level. The steps of this laboratory research are operated through phytochemical screening and testing the cytotoxic effect of the Brine Shrimp Lethality Test (BSLT) method on Artemia salina Leach larvae samples. The procedure for determining lethal potential is executed in a structured manner by measuring the % mortality of larvae which is then calculated via linear probit statistical analysis. Quantitative data empirically reveals the presence of secondary metabolites in the form of flavonoids, saponins, tannins, triterpenoids, and coumarins. The results of the toxicity test recorded an LC50 parameter value of 9,852.74 μg/mL. The main conclusion confirms that the liquid extract of red banana stem is classified as very safe (non-toxic) because the LC50 value is above the threshold of 1,000 μ